Effects of local anesthetics on wound healing - Kesici,Sevgi (2018)
Abstract Introduction Local anesthetic infiltration is used widely for post-operative analgesia in many situations. However the effects of local anesthetics on wound healing are not demonstrated clearly. This study planned to evaluate the effects of lidocaine, prilocaine, bupivacaine and levobupivacaine on wound healing, primarily on wound tensile strength and on collagen ultrastructure. Methods This study was conducted on male Sprague Dawley rats. On days 0, 8th, 15th, and 21st, all animals were weighed and received a preincisional subcutaneous infiltration of 3 mL of a solution according the group. Control saline (C), lidocaine (L) 7 mg.kg-1, prilocaine (P) 2 mg.kg-1, bupivacaine (B) 2 mg.kg-1 and levobupivacaine (LVB) 2.5 mg.kg-1. The infiltrations were done at the back region 1.5 cm where incision would be performed at the upper, middle and lower part along the midline, under general anesthesia. Wound tensile strengths were measured after 0.7 cm × 2 cm of cutaneous and subcutaneous tissue samples were obtained vertical to incision from infiltrated regions. Tissue samples were also obtained for electron microscopic examination. Evaluations were on the 8th, 15th and 21st days after infiltration. Results There was no difference between groups in the weights of the rats at the 0th, 8th, 15th and 21st days. The collagen maturation was no statistically different between groups at the 8th and 15th days. The maturation scores of the B and L groups at the 21st day was significantly lower than the Group C (1.40, 1.64 and 3.56; respectively). The wound tensile strength was no statistically different between groups at the 8th and 15th days but at the 21st day the Groups B and LVB had significantly lower value than Group C (5.42, 5.54 and 6.75; respectively). Conclusion Lidocaine and prilocaine do not affect wound healing and, bupivacaine and levobupivacaine affect negatively especially at the late period.